Quantifying coral-algal interactions in an acidified ocean: Sargassum spp. exposure mitigates low pH effects on Acropora cervicornis health - Johann D. Lankes; Johann D. Lankes; Heather N. Page; Amanda Quasunella; Jaclyn F. Torkelson; Clöe Lemaire; Robert J. Nowicki; Lillia Blasius; Emily R. Hall; Emily R. Hall (Frontiers in Marine Science)
Increasingly frequent large-scale pelagic Sargassum algae blooms in the Atlantic have become a problem for coastal ecosystems. The mass decay of these blooms reduces water quality for coastal flora and fauna. However, the effects of living Sargassum blooms on seawater quality and consequently coral reef ecosystems that rely on delicately balanced carbonate chemistry are more ambiguous. Future oceans are predicted to be more acidic as additional anthropogenic CO2 emissions are absorbed, potentially tipping the balance in favor of algal blooms at the cost of coral survival. This study aimed to simulate the indirect interaction between pelagic Sargassum spp. and Acropora cervicornis coral fragments from the Florida Reef in current-day and future ocean pH conditions over the course of 70 days in a mesocosm experimental system. Measurements of coral growth and health via buoyant weight and Pulse Amplitude Modulated (PAM) fluorescence measurements reveal an unexpected coral-algal interaction. After 1 month, coral growth was significantly reduced under ocean acidification conditions and exposure to Sargassum; at the same time quantum yield and maximum electron transport rate of photosynthesis were increased relative to control counterparts in ambient and future pH scenarios by up to 14% and 18% respectively. These improvements in photosynthetic efficiency did not translate to significant differences in growth by the final measurement time point. In addition, the presence of Sargassum spp. did not raise seawater pH in the system, raising questions about how it benefited photosynthetic efficiency in exposed corals. Heterotrophy of detrital algal matter is suspected to compensate for impaired photosynthesis of pH stressed corals. Therefore, despite their current negative reputation, Sargassum blooms could provide short term localized benefits to corals in present and future ocean conditions.